Polyolefin microporous membrane
The polyolefin microporous membrane with a controlled film thickness reduction rate and phase-separated structure addresses the balance between compression resistance and shutdown characteristics, enhancing the safety and performance of secondary batteries.
Patent Information
- Application Number
- JP2020212077
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-12-22
AI Technical Summary
Existing microporous polyolefin membranes used as separators in secondary batteries face challenges in balancing compression resistance with shutdown characteristics, leading to compromised charge/discharge performance and safety due to issues like pore compression and thermal instability.
A polyolefin microporous membrane with specific film thickness reduction rate/porosity, porosity, and phase-separated structure, incorporating a polyethylene resin and an incompatible polymer, such as a cyclic olefin polymer, to enhance compression resistance and shutdown performance.
The membrane achieves high compression resistance and rapid shutdown at lower temperatures, ensuring excellent charge/discharge characteristics and safety when used as a battery separator.
Smart Images

Figure 0007604877000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a microporous polyolefin membrane, and more particularly to a microporous polyolefin membrane that has excellent charge / discharge characteristics and battery safety when used as a separator for a secondary battery. [Background technology]
[0002] Microporous membranes are used in various fields, such as filters such as filtration membranes and dialysis membranes, separators for secondary batteries, separators for electrolytic capacitors, etc. Among these, polyolefin microporous membranes made of polyolefin as a resin material are widely used in recent years as separators for secondary batteries because of their excellent chemical resistance, insulating properties, mechanical strength, and shutdown properties.
[0003] Because of their high energy density, secondary batteries, such as lithium-ion secondary batteries, are widely used in personal computers, mobile phones, etc. Secondary batteries are also expected to be used as power sources for driving motors in electric and hybrid vehicles, and as stationary storage batteries.
[0004] In recent years, the energy density of lithium-ion secondary batteries has been increasing. Some new electrode materials designed for high energy density have the characteristic of easily expanding during charging. As a result, pressure is applied to the separator during charging, compressing the pores and releasing the electrolyte, which deteriorates the charge-discharge characteristics. In addition, the battery manufacturing process sometimes involves a pressing process to mold the cells and improve the adhesion between the components, but this can sometimes cause the pores in the separator to collapse, impairing the ion permeability of the separator. Due to these issues, there is a demand for improved compression resistance in separators.
[0005] On the other hand, the electrodes used in lithium-ion secondary batteries designed for high energy density tend to have low thermal stability. Therefore, in the event of abnormal heat generation due to short circuit or overcharging, it is required to prevent thermal runaway by shutting down the separator (blocking pores) at a lower temperature and preventing ion migration between the positive and negative electrodes.
[0006] The compression resistance of a microporous membrane can be improved by increasing the membrane strength through the raw material formulation and stretching conditions. However, increasing the strength of the membrane leads to a higher melting point of the resin, which deteriorates the shutdown property. For this reason, it has been difficult to achieve both compression resistance and shutdown property.
[0007] Patent Document 1 proposes a microporous membrane with excellent compression resistance, for example, by using a specific raw material formulation, such as by incorporating ultra-high molecular weight polyethylene and / or a nucleating agent, or by adjusting the weight-average molecular weight Mw or the stretching ratio.
[0008] In Patent Document 2, polyolefin having a viscosity average molecular weight (Mv) of less than 300,000, polyolefin having an Mv of 500,000 or more, and electrochemically inactive particles larger than the film thickness are essential components, and a thickness of the film is determined by dividing the thickness of the film by the height A (μm) of the part where the particles protrude from the film surface by the thickness B (μm).
[0009] Patent Document 3 proposes that a polyolefin microporous membrane having an air permeability increase of 500 seconds / 100 cc or less after being heated and compressed at 90°C for 5 minutes under a pressure of 5 MPa has an excellent balance of heat compression resistance, permeability, mechanical properties, and heat shrinkability. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] International Publication No. 2018 / 164056 [Patent Document 2] JP 2007-262203 A [Patent Document 3] JP 2004-161899 A Summary of the Invention [Problem to be solved by the invention]
[0011] In contrast to Patent Document 1, for example, while high-ratio stretching is essential to improve compression resistance, this is accompanied by a high melting point of the resin. Therefore, improvement is desired in consideration of compatibility with the shutdown temperature. In Patent Document 2, there is concern that coarse particles form coarse pores, which may deteriorate shutdown characteristics. Patent Document 3 describes the film thickness after release from heat compression, but does not discuss separator deformation during heat compression.
[0012] An object of the present invention is to solve the above problems by providing a polyolefin microporous membrane that, when used as a battery separator, has excellent charge / discharge characteristics due to high compression resistance, and can quickly shut down the battery when it abnormally heats up, thereby providing high safety. [Means for solving the problem]
[0013] In order to solve the above problems and achieve the object, the present invention has the following configuration. In the following description, a numerical range expressed using "~" means a range including the numerical values before and after "~" as the lower and upper limits. [1] A microporous polyolefin membrane having a membrane thickness reduction rate / porosity ratio of 0.20 or less when pressurized at 70°C and 2.3 MPa, and a shutdown temperature of 140°C or less. [2] The polyolefin microporous membrane according to [1] above, having a porosity of 35% or more. [3] The polyolefin microporous membrane according to [1] or [2] above, which has a porosity of 30% or more when pressurized at 70°C and 2.3 MPa. [4] The microporous polyolefin film according to any one of the above [1] to [3], comprising 50 to 99 mass % of a polyethylene resin and 1 to 50 mass % of a polymer incompatible with the polyethylene resin. [5] The polyolefin microporous membrane according to [4] above, wherein the polymer incompatible with the polyethylene resin is an amorphous polymer. [6] The polyolefin microporous membrane according to [4] above, wherein the polymer incompatible with the polyethylene resin is a cyclic olefin polymer. [7] The polyolefin microporous membrane according to any one of the above [1] to [6], wherein a first phase made of a polyethylene-based resin has a continuous structure, and a second phase made of a polymer incompatible with the polyethylene-based resin has a discontinuous structure, and the second phase has a domain diameter of 10 to 300 nm. [8] The microporous polyolefin film according to any one of the above [1] to [7], which has a heat shrinkage rate of 5% or less after 8 hours at 105°C. [9] Air permeability per 1 μm thickness is 30 sec / 100 cm 3 The microporous polyolefin membrane according to any one of the above items [1] to [8], which is:
[10] The microporous polyolefin film according to any one of the above [1] to [9], which has a pin puncture strength of 10 gf / μm or more per 1 μm thickness.
[11] The microporous polyolefin film according to any one of the above [1] to
[10] , which has a thickness of 5 μm or more. Effect of the Invention
[0014] The polyolefin microporous membrane of the present invention has high compression resistance and a performance of shutting down (pore blocking) at a lower temperature, and therefore, when used as a separator for a secondary battery, it can provide a polyolefin microporous membrane with excellent charge / discharge characteristics and safety. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described. However, the present invention is not limited to the embodiment described below.
[0016] The polyolefin microporous membrane according to an embodiment of the present invention (hereinafter sometimes simply referred to as "microporous membrane") has a membrane thickness reduction rate / porosity ratio of 0.20 or less when pressurized at 70°C and 2.3 MPa, and a shutdown temperature of 140°C or less.
[0017] The value represented by the film thickness reduction rate / porosity when pressurized at 70°C and 2.3 MPa (hereinafter, sometimes simply referred to as "film thickness reduction rate / porosity") can be measured and calculated by the method described below. The film thickness reduction rate / porosity is 0.20 or less, preferably 0.18 or less, more preferably 0.15 or less, even more preferably 0.12 or less, and particularly preferably 0.10 or less. When the film thickness reduction rate / porosity is in the above range, the film thickness reduction rate / porosity is excellent in compression resistance. That is, when the microporous membrane is used as a battery separator, even if the separator is in a pressurized state during electrode expansion or press processing, the pore structure and permeability are maintained, and a battery with excellent charge / discharge characteristics can be obtained. The lower limit of the film thickness reduction rate / porosity is not particularly limited, but is, for example, 0.01 or more. By setting the lower limit of the film thickness reduction rate / porosity in the above range, it is easy to achieve compatibility with the shutdown temperature. To set the membrane thickness reduction rate / porosity within the above range, it is preferable that the raw material composition of the microporous membrane is within the range described below, and the membrane production conditions for the microporous membrane are within the range described below.
[0018] The shutdown temperature of the polyolefin microporous membrane according to the embodiment of the present invention is 140°C or less. It is preferably 139°C or less, more preferably 138°C or less, even more preferably 136°C or less, and particularly preferably 134°C or less. By controlling the shutdown temperature within the above range, the battery safety is excellent when used as a battery separator. The lower limit of the shutdown temperature is not particularly limited, but it is preferably 110°C or more because it is easy to achieve compatibility with permeability. In order to set the shutdown temperature within the above range, it is preferable that the raw material composition of the microporous membrane is within the range described below, and the film-forming conditions of the microporous membrane are within the range described below. The shutdown temperature is a temperature measured by the method described below, and is a temperature at which the resin part shrinks and melts when the polyolefin microporous membrane is heated, closing the porous structure, and substantially discharging and charging are not possible when used as a battery separator.
[0019] The porosity of the polyolefin microporous membrane according to the embodiment of the present invention is preferably 35% or more, more preferably 40% or more, even more preferably 45% or more, and particularly preferably 50% or more. There is no particular upper limit to the porosity, but it is preferably 80% or less because it can suppress a decrease in membrane strength. When the porosity is in the above range, the microporous membrane has excellent output characteristics when used as a separator for a secondary battery. The porosity can be adjusted to the above range by adjusting the blending ratio of the raw materials, the stretching ratio, the heat setting conditions, etc. in the production process.
[0020] The porosity of the polyolefin microporous membrane according to the embodiment of the present invention when pressurized at 70°C and 2.3 MPa is preferably 30% or more, more preferably 33% or more, even more preferably 40% or more, and particularly preferably 45% or more. There is no particular upper limit for the porosity when pressurized at 70°C and 2.3 MPa, but it is preferably 80% or less because it can suppress a decrease in membrane strength. When the porosity when pressurized at 70°C and 2.3 MPa is in the above range, the microporous membrane has excellent output characteristics when used as a separator for a secondary battery. The porosity when pressurized at 70°C and 2.3 MPa can be set to the above range by adjusting the blending ratio of raw materials, the stretching ratio, the heat setting conditions, etc. in the manufacturing process. The porosity when pressurized at 70°C and 2.3 MPa can be measured and calculated by the method described below.
[0021] In the polyolefin microporous membrane according to the embodiment of the present invention, the first phase made of a polyethylene resin preferably has a continuous structure, and the second phase made of a polymer incompatible with the first phase preferably has a discontinuous structure. The domain diameter of the second phase forming the discontinuous structure is preferably 10 to 300 nm, particularly preferably 20 nm or more, more preferably 250 nm or less, and particularly preferably 150 nm or less.
[0022] The second phase has the above-mentioned domain diameter, so that a uniform pore structure is formed, and the polyolefin microporous membrane is improved in both compression resistance and high permeability. The phase separation structure in the microporous membrane can be observed by the method described below, and the domain diameter can be calculated. The domain diameter of the second phase forming a discontinuous structure can be set to the above range by adjusting the resin components forming the second phase, the blending ratio thereof in the manufacturing process, the kneading conditions, the stretching conditions, etc.
[0023] The polyolefin microporous membrane according to the embodiment of the present invention has a heat shrinkage ratio before and after heating at 105°C for 8 hours of preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less. There is no particular lower limit for the heat shrinkage ratio after 8 hours at 105°C, but it is preferably -0.1% or more because the flatness of the microporous membrane is good. By setting the heat shrinkage ratio after 8 hours at 105°C in the above range, when the microporous membrane is used as a battery separator, it is possible to suppress end short-circuiting due to shrinkage during heat generation. The heat shrinkage ratio after 8 hours at 105°C can be calculated by the method described below. The heat shrinkage ratio after 8 hours at 105°C can be set to the above range by adjusting the blending ratio of raw materials, the stretch ratio, the heat setting conditions, etc. in the production process.
[0024] The polyolefin microporous membrane according to the embodiment of the present invention preferably has an air permeability of 30 sec / 100 cm per 1 μm thickness. 3 Less than 20 seconds / 100cm, more preferably 3 Less than 15 seconds / 100 cm, more preferably 3 Less than 10 seconds / 100 cm is particularly preferable. 3 There is no particular lower limit for the air permeability converted into a thickness of 1 μm, but since this makes it easier to achieve compatibility with the membrane strength, it is set to 1 sec / 100 cm 3 It is preferable that the air permeability is equal to or greater than the above range. By setting the air permeability in terms of 1 μm thickness within the above range, a microporous membrane having excellent charge / discharge characteristics can be obtained when used as a battery separator. The air permeability in terms of 1 μm thickness can be set within the above range by adjusting the blending ratio of the raw materials, the stretching ratio, the heat setting conditions, and the like in the production process.
[0025] The polyolefin microporous membrane according to the embodiment of the present invention has a puncture strength calculated based on a thickness of 1 μm of preferably 10 gf / μm or more, more preferably 15 gf / μm or more, even more preferably 20 gf / μm or more, and particularly preferably 30 gf / μm or more. The upper limit of the puncture strength calculated based on a thickness of 1 μm is not particularly limited, but it is preferably 100 gf / μm or less, for example, because it is easy to control the shutdown temperature within an appropriate range. When the puncture strength calculated based on a thickness of 1 μm is within the above range, the microporous membrane is resistant to external impacts and has excellent safety when used as a battery separator. The puncture strength calculated based on a thickness of 1 μm can be adjusted to the above range by adjusting the blending ratio of raw materials, the stretching ratio, the heat setting conditions, etc. in the manufacturing process.
[0026] The tensile strength (tensile breaking strength) in the MD direction of the polyolefin microporous membrane is preferably 50 MPa or more, more preferably 100 MPa or more, and even more preferably 200 MPa or more. The upper limit of the tensile strength in the MD direction is not particularly limited, but is, for example, 500 MPa or less, since it is easy to achieve compatibility with the shutdown temperature. When the tensile strength in the MD direction is within the above range, the membrane is unlikely to break even when a high tension is applied in the MD direction, and can be used for applications requiring high durability.
[0027] The tensile strength (tensile breaking strength) in the TD direction of the polyolefin microporous membrane is preferably 50 MPa or more, more preferably 100 MPa or more, and even more preferably 200 MPa or more. The upper limit of the tensile strength in the TD direction is not particularly limited, but is, for example, 500 MPa or less, since it is easy to achieve compatibility with the shutdown temperature. When the tensile strength in the TD direction is in the above range, the membrane is unlikely to break even when a high tension is applied in the TD direction, and can be used for applications requiring high durability.
[0028] In the polyolefin microporous membrane, the ratio of MD tensile strength to TD tensile strength (MD tensile strength / TD tensile strength) is preferably 0.5 or more, more preferably 0.6 or more, even more preferably 0.7 or more, and particularly preferably 0.8 or more. In addition, this ratio is preferably 2.0 or less, more preferably 1.7 or less, even more preferably 1.5 or less, and particularly preferably 1.3 or less. By setting the ratio of MD tensile strength to TD tensile strength in the above range, when the microporous membrane is used as a battery separator, it is resistant to external impact and has excellent safety.
[0029] The thickness of the polyolefin microporous membrane according to the embodiment of the present invention can be appropriately adjusted depending on the application. It is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 10 μm or more. It is also preferably 30 μm or less, more preferably 28 μm or less, even more preferably 25 μm or less, and particularly preferably 21 μm or less. By setting the thickness of the polyolefin microporous membrane within the above range, both safety and high battery capacity can be achieved when used as a separator for a secondary battery.
[0030] Hereinafter, a specific configuration of the polyolefin microporous membrane of the present embodiment will be described, but the present invention is not necessarily limited thereto.
[0031] The polyolefin microporous membrane according to the embodiment of the present invention contains a polyolefin resin as a main component (hereinafter, the polyolefin resin as the main component is referred to as "resin A"). The main component here refers to the component constituting the polyolefin microporous membrane that has the largest content in mass %. When two or more polyolefin resins that are resin A are contained, the total content of those polyolefin resins is defined as the content of resin A, and this total content may be the one that has the largest content in mass % among the components constituting the polyolefin microporous membrane.
[0032] Examples of resin A include polyethylene-based resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ultra-high molecular weight polyethylene, and low-crystalline or amorphous ethylene-α-olefin copolymers; polypropylene-based resins such as homopolypropylene, propylene-ethylene copolymers (random copolymers and / or block copolymers), propylene-α-olefin copolymers, and propylene-ethylene-α-olefin copolymers; and cyclic olefin-based resins containing alicyclic structures such as cycloalkanes and cycloalkenes as repeating units. The α-olefin is not particularly limited as long as it can be copolymerized with propylene or ethylene, and examples thereof include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-pentene, and 1-heptene. Among the above-mentioned resins, resin A preferably contains a polyethylene-based resin, and more preferably contains high-density polyethylene and ultra-high molecular weight polyethylene, from the viewpoint of achieving both compression resistance and shutdown characteristics. Resin A may be selected from two or more of the above-mentioned resins.
[0033] Resin A was selected from the viewpoints of melt extrusion properties and stretch processing properties, and high-density polyethylene (density: 0.940 g / m 3 More than 0.970g / m 3 It is preferable that the polyethylene resin used for resin A (hereinafter, sometimes referred to as "polyethylene (A)") is not only an ethylene homopolymer, but also a copolymer containing other α-olefins in order to lower the melting point and crystallinity of polyethylene (A). Examples of α-olefins include propylene, butene-1, hexene-1, pentene-1, 4-methylpentene-1, octene, vinyl acetate, methyl methacrylate, and styrene. As a copolymer containing an α-olefin, a copolymer containing hexene-1 (ethylene-1-hexene copolymer) is preferable, and it is more preferable that polyethylene (A) is mainly composed of an ethylene-1-hexene copolymer. In addition, the α-olefin is 13This can be confirmed by measuring with C-NMR. The main component shown here refers to the component that constitutes the polyethylene (A) and that has the highest content, expressed as mass %, of the components.
[0034] The lower limit of the weight average molecular weight of the high density polyethylene is preferably 1×10 4 More preferably, it is 1×10 5 More preferably, 1.5×10 5 The upper limit of the weight average molecular weight of the high-density polyethylene is preferably 1×10 6 Less than or equal to 8.0×10 5 Less than 6.0×10, more preferably 5 By setting the weight average molecular weight of the branched high-density polyethylene within the above range, it is possible to achieve both a low shutdown temperature and a high film strength during shutdown.
[0035] The melting point of the branched high-density polyethylene is preferably 138° C. or lower, more preferably 136° C. or lower, and even more preferably 134° C. or lower. The melting point is preferably 115° C. or higher, more preferably 120° C. or higher, and even more preferably 125° C. or higher. By setting the melting point of the high-density polyethylene within the above range, both a low shutdown temperature and good permeability of the polyolefin microporous membrane can be achieved.
[0036] Resin A preferably contains branched high-density polyethylene, because it can form a uniform fine pore structure and inhibit crystal orientation during stretching to produce a polyolefin microporous film with excellent compression resistance and shutdown characteristics. Branched high-density polyethylene is polyethylene polymerized using a catalyst in which a chromium compound is supported on a support made of an inorganic compound such as silica or alumina.
[0037] The branched high-density polyethylene is contained in an amount of preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the total mass of resin A. This allows a polyolefin microporous membrane with improved compression resistance and shutdown properties to be obtained.
[0038] The lower limit of the weight average molecular weight of the branched high-density polyethylene is preferably 1×10 4 More preferably, it is 1×10 5 More preferably, 1.5×10 5 The upper limit of the weight average molecular weight of the high-density polyethylene is preferably 1×10 6 Less than or equal to 8.0×10 5 Less than 6.0×10, more preferably 5 By setting the weight average molecular weight of the branched high-density polyethylene within the above range, it is possible to achieve both a low shutdown temperature and a high film strength during shutdown.
[0039] The melting point of the branched high-density polyethylene is preferably 138°C or lower, more preferably 136°C or lower, and even more preferably 134°C or lower. The melting point is preferably 115°C or higher, more preferably 120°C or higher, and even more preferably 125°C or higher. By setting the melting point of the branched high-density polyethylene within the above range, both a low shutdown temperature and good permeability of the polyolefin microporous membrane can be achieved. The melting point of the branched high-density polyethylene can be measured by the method described below.
[0040] The content of resin A in the polyolefin microporous membrane is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and is preferably 99% by mass or less, more preferably 97% by mass or less, even more preferably 95% by mass or less. By setting the content of resin A in the polyolefin microporous membrane within the above range, it becomes easy to control the strength, permeability, and shutdown properties of the microporous membrane, and the microporous membrane has better compression resistance.
[0041] In addition, when preparing a polyolefin resin composition for producing a polyolefin microporous membrane, a membrane-forming solvent such as liquid paraffin is used as a plasticizer.Since such membrane-forming solvent is removed during the production process of a microporous membrane, the composition of the polyolefin resin composition is different from the composition of the polyolefin microporous membrane.In other words, the content of resin A in a polyolefin microporous membrane corresponds to the content of resin A relative to the composition of the polyolefin resin composition excluding the components to be removed such as membrane-forming solvent.
[0042] From the viewpoint of achieving both compression resistance and shutdown characteristics, the microporous polyolefin membrane according to an embodiment of the present invention preferably contains a resin (hereinafter referred to as "resin B") that is a polymer incompatible with resin A.
[0043] It is preferable that resin B is incompatible with resin A and forms a phase-separated structure in the microporous membrane. As resin B, either a crystalline polymer resin or an amorphous polymer resin can be used.
[0044] Examples of the crystalline polymer include polypropylene resins such as homopolypropylene, propylene-ethylene copolymers (random copolymers and / or block copolymers), propylene-α-olefin copolymers, and propylene-ethylene-α-olefin copolymers, polymethylpentene, polyester resins, polyamides, polyacetals, fluororesins, polyphenylene sulfide, and polyether ether ketones. The above-mentioned α-olefins are not particularly limited as long as they can be copolymerized with propylene or ethylene, and examples of the α-olefins include 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-pentene, and 1-heptene.
[0045] Examples of amorphous polymers include cyclic olefin polymers containing alicyclic structures such as cycloalkane and cycloalkene as repeating units, polyvinyl chloride, acrylic resins, polycarbonates, polystyrene, polybutadienes, styrene-based elastomers, polysulfones, ABS resins, and silicone resins.
[0046] Of the above-mentioned resins, it is preferable to use a resin that is an amorphous polymer as the resin B, and a resin that is a cyclic olefin polymer is more preferable.
[0047] By selecting Resin B from the above-mentioned polymers, a uniform and fine domain structure is formed in the microporous membrane. When the microporous membrane is used as a battery separator, the compression resistance of the microporous membrane is further improved without impairing battery performance, such as ion permeability, or battery safety performance, such as shutdown characteristics.
[0048] When a resin that is an amorphous polymer is used as resin B, the glass transition temperature of resin B is preferably 60° C. or higher, more preferably 80° C. or higher, even more preferably 100° C. or higher, and particularly preferably 120° C. or higher. The glass transition temperature is preferably 250° C. or lower, more preferably 200° C. or lower, even more preferably 180° C. or lower, and particularly preferably 150° C. or lower. By setting the glass transition temperature of resin B within the above range, a phase-separated structure consisting of resin A phase, resin B phase, and plasticizer phase is formed uniformly and finely when the molten and kneaded resin is cooled, and the obtained microporous membrane has excellent compression resistance.
[0049] The content of resin B in the polyolefin microporous membrane is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. It is also preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more. By setting the content of resin B in the above range, it becomes easy to control the balance between compression resistance and permeability.
[0050] The layer structure of the polyolefin microporous membrane according to the embodiment of the present invention may be a single layer membrane or a laminate membrane composed of at least two layers having different properties. In the case of a laminate membrane, at least one layer is preferably composed of the above-mentioned resin A and resin B.
[0051] The polyolefin microporous membrane according to the embodiment of the present invention may be provided with a coating layer. The coating layer may be a porous layer other than polyolefin resin. The other porous layer is not particularly limited, but is preferably, for example, a porous layer such as an inorganic particle layer containing a binder and inorganic particles.
[0052] The binder component constituting the inorganic particle layer is not particularly limited, and any known component can be used. For example, an acrylic resin, a polyvinylidene fluoride resin, a polyamideimide resin, a polyamide resin, an aromatic polyamide resin, a polyimide resin, or the like can be used.
[0053] The inorganic particles constituting the inorganic particle layer are not particularly limited, and known materials can be used, such as alumina, boehmite, barium sulfate, magnesium oxide, magnesium hydroxide, magnesium carbonate, and silicon.
[0054] Next, the method for producing the polyolefin microporous membrane in the embodiment of the present invention will be described. The method for producing the polyolefin microporous membrane can be, for example, a dry membrane production method or a wet membrane production method. As the method for producing the polyolefin microporous membrane in the present embodiment, the wet membrane production method is preferred from the viewpoint of controlling the structure and physical properties of the membrane.
[0055] A wet method for producing a polyolefin microporous membrane will be described below. Note that the following description is merely an example of the production method, and the present invention is not limited to this method.
[0056] A method for producing a polyolefin microporous membrane in an embodiment of the present invention preferably includes the following steps (1) to (5) in this order, and may further include the following step (6). After or instead of step (6), the method may further include at least one of the following steps (7) and (8).
[0057] (1) A step of melt-kneading the polyolefin resin and a membrane-forming solvent to prepare a polyolefin resin composition. (2) A step of extruding the polyolefin resin composition and cooling it to form a gel-like sheet. (3) A first stretching step of preheating and stretching the gel-like sheet (4) A step of removing the membrane-forming solvent from the stretched gel-like sheet. (5) A step of drying the sheet after removing the membrane-forming solvent. (6) A second stretching step of preheating and stretching the dried sheet (7) A step of heat treating the dried sheet (8) A step of subjecting the dried sheet to a crosslinking treatment and / or hydrophilization treatment. (1) Preparation of polyolefin resin composition Resin A and resin B are heated and dissolved in a plasticizer (membrane-forming solvent) to prepare a polyolefin resin composition. The plasticizer is not particularly limited as long as it can uniformly disperse resin A and resin B, but in order to enable relatively high-magnification stretching, it is preferable that the solvent is liquid at room temperature. Examples of the solvent include aliphatic, cycloaliphatic, or aromatic hydrocarbons such as nonane, decane, decalin, paraxylene, undecane, dodecane, and liquid paraffin, and mineral oil fractions having boiling points corresponding thereto, as well as phthalic acid esters that are liquid at room temperature, such as dibutyl phthalate and dioctyl phthalate. In order to obtain a gel-like sheet with a stable content of the liquid solvent, it is preferable to use a nonvolatile liquid solvent such as liquid paraffin.
[0058] The blending ratio of resin A, resin B, and plasticizer may be appropriately selected within a range that does not impair moldability, but the total content of resin A and resin B is preferably 10 to 50 mass% relative to the total mass of the polyolefin resin composition. If the total content of resin A and resin B is 10 mass% or more, swelling and necking at the outlet of the die are not large when molding into a sheet, and the moldability and film-forming properties of the sheet are good. On the other hand, if the total content of resin A and resin B is 50 mass% or less, shrinkage in the thickness direction is suppressed, and moldability is good.
[0059] The content of resin B in the polyolefin resin composition is preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less. The content of resin B is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more. By setting the content of resin B in the polyolefin resin composition within the above range, resin B can be well dispersed in the polyolefin resin composition, and a polyolefin microporous film with better compression resistance can be obtained.
[0060] The method for uniformly melt-kneading the resin A, the resin B, and the plasticizer is not particularly limited, but is preferably carried out in a twin-screw extruder.
[0061] The resin temperature during kneading is preferably 140° C. or higher, more preferably 150° C. or higher, and even more preferably 160° C. or higher, with the upper limit being preferably 250° C. or lower, more preferably 240° C. or lower, and even more preferably 230° C. or lower. By keeping the temperature of the polyolefin resin composition during kneading within the above range, it is possible to prevent a decrease in strength due to deterioration of the resin, and it is possible to uniformly melt-knead Resin A, Resin B, and the plasticizer.
[0062] In addition, during kneading with a twin-screw extruder, the Q / Ns calculated from the ratio of the extrusion mass Q (kg / hr) to the screw rotation speed Ns (rpm) is preferably 0.01 or more, more preferably 0.05 or more, and even more preferably 0.1 or more. This can prevent a decrease in strength due to resin deterioration during kneading. In addition, the upper limit is preferably 5.0 or less, more preferably 3.0 or less, and even more preferably 2.0 or less, which allows sufficient shear to be applied to the polyolefin resin composition, resulting in a uniform dispersion state.
[0063] (2) Gel-like sheet formation process The melt of the polyolefin resin composition is fed from the extruder to a die and extruded into a sheet.
[0064] The extrusion method may be either a flat die method or an inflation method. A plurality of polyolefin resin compositions having the same or different compositions may be fed from a plurality of extruders to a single multi-manifold type composite T-die, laminated in layers, and extruded into a sheet having a laminated structure. The extrusion temperature is preferably 140 to 250°C, and the extrusion speed is preferably 0.2 to 15 m / min.
[0065] The resin composition melt-extruded into a sheet is cooled and solidified to become a gel-like sheet. In the cooling step, it is preferable to cool to 10 to 50°C. This is because it is preferable to set the final cooling temperature below the crystallization end temperature, and by making the high-order structure finer, it becomes easier to perform uniform stretching in the subsequent stretching. In addition, the cooling rate at this time is preferably performed at a rate of 50°C / min or more, more preferably 100°C / min or more, and even more preferably 150°C / min or more. In general, when the cooling rate is slow, relatively large crystals are formed, so the high-order structure of the gel-like sheet becomes coarse, and the gel structure that forms it also becomes large. On the other hand, when the cooling rate is fast, relatively small crystals are formed, so the high-order structure of the gel-like sheet becomes dense, which leads to uniform stretching as well as improved strength and elongation of the film. The cooling method at this time includes a method of directly contacting the sheet with cold air, cooling water, or other cooling medium, a method of contacting a roll cooled with a refrigerant, a method using a casting drum, etc.
[0066] (3) First stretching step Next, the obtained gel-like sheet is stretched at least uniaxially, but it is preferable to preheat the gel-like sheet before stretching. The preheating temperature is preferably 90 to 130°C, more preferably 105°C or higher, even more preferably 110°C or higher, and more preferably 120°C or lower, even more preferably 117°C or lower. By preheating under the above conditions, a polyolefin microporous membrane that is uniformly stretched in the stretching step and has a uniform and fine pore structure can be obtained.
[0067] The gel-like sheet after preheating is preferably stretched at a predetermined ratio by a tenter method, a roll method, an inflation method, or a combination of these. The stretching may be uniaxial or biaxial, but biaxial stretching is preferred. In the case of biaxial stretching, any of simultaneous biaxial stretching, sequential biaxial stretching, and multi-stage stretching (for example, a combination of simultaneous biaxial stretching and sequential biaxial stretching) may be used, but sequential biaxial stretching is preferred from the viewpoint of increasing compression resistance.
[0068] The stretching ratio (area stretching ratio) in this step is preferably 16 times or more, more preferably 25 times or more, and particularly preferably 49 times or more. In addition, it is preferably 4 times or more in both the machine longitudinal direction (MD direction) and the machine width direction (TD direction), and more preferably 5 times or more. The stretching ratios in the MD direction and the TD direction may be the same or different from each other. By setting the area stretching ratio within the above range, mechanical strength and permeability can be increased. In addition, the area stretching ratio in this step is preferably 150 times or less, more preferably 100 times or less, which can prevent membrane rupture and suppress an increase in the shutdown temperature. The stretching ratio in this step refers to the area stretching ratio of the polyolefin microporous membrane immediately before being subjected to the next step, based on the polyolefin microporous membrane immediately before this step.
[0069] The stretching temperature in this step is preferably within the range of the crystal dispersion temperature (TCD) of the polyolefin resin to (TCD+30)° C., more preferably at least (TCD+5)° C., particularly preferably at least (TCD+10)° C., and more preferably at most (TCD+28)° C., particularly preferably at most (TCD+26)° C. When the stretching temperature is within the above range, film rupture due to stretching of the polyolefin resin is suppressed, and high-magnification stretching is possible.
[0070] The crystal dispersion temperature (TCD) is determined by measuring the temperature characteristics of dynamic viscoelasticity according to ASTM D 4065. When a polyethylene resin is used as the polyolefin resin, ultra-high molecular weight polyethylene, polyethylene other than ultra-high molecular weight polyethylene, and polyethylene resin compositions have crystal dispersion temperatures of about 100 to 110°C, so the stretching temperature is preferably 90 to 130°C, more preferably 105°C or higher, even more preferably 110°C or higher, more preferably 120°C or lower, and even more preferably 117°C or lower.
[0071] The stretching process causes cleavage between the polyethylene lamellae, resulting in the polyethylene resin phase becoming finer and the formation of numerous fibrils. The fibrils form a three-dimensionally irregularly connected network structure.
[0072] (4) Removal of membrane-forming solvent The membrane-forming solvent is removed (washed) using a washing solvent. The polyolefin resin phase is phase-separated from the membrane-forming solvent phase. Therefore, when the membrane-forming solvent is removed, a porous membrane is obtained that is made of fibrils that form a fine three-dimensional network structure and has holes (voids) that are three-dimensionally irregularly connected. Washing solvents and methods for removing the membrane-forming solvent using the same are publicly known, so a description thereof will be omitted. For example, the methods disclosed in Japanese Patent No. 2132327 and Japanese Patent Laid-Open No. 2002-256099 can be used.
[0073] (5) Drying process The polyolefin microporous membrane from which the membrane-forming solvent has been removed is dried by heat drying or air drying. The drying temperature is preferably equal to or lower than the crystal dispersion temperature (TCD) of the polyolefin resin, and more preferably 5° C. or more lower than the TCD. The drying is preferably carried out until the amount of the remaining washing solvent is 5 parts by mass or less, more preferably 3 parts by mass or less, per 100 parts by mass (dry mass) of the total mass of the polyolefin microporous membrane.
[0074] (6) Second stretching step The dried polyolefin microporous membrane may be stretched at least uniaxially (second stretching step). The polyolefin microporous membrane may be preheated before the second stretching step. The preheating temperature is preferably 90 to 140°C, more preferably 95°C or higher, even more preferably 100°C or higher, and more preferably 135°C or lower, even more preferably 130°C or lower. The polyolefin microporous membrane may be stretched while being heated by a tenter method, a roll method, an inflation method, or the like, as described above. The stretching may be uniaxial or biaxial. In the case of biaxial stretching, any of simultaneous biaxial stretching, sequential biaxial stretching, and multi-stage stretching (for example, a combination of simultaneous biaxial stretching and sequential biaxial stretching) may be used.
[0075] The stretching temperature in this step is not particularly limited, but is usually 90 to 140°C, more preferably 95°C or higher, further preferably 100°C or higher, and more preferably 130°C or lower.
[0076] The area stretching ratio in this step is preferably 16.0 times or less, more preferably 4.0 times or less, and even more preferably 2.0 times or less. In the case of biaxial stretching, the stretching ratios in the MD direction and the TD direction may be the same or different. The stretching ratio in this step refers to the stretching ratio of the polyolefin microporous membrane immediately before the step, based on the polyolefin microporous membrane immediately before the step.
[0077] (7) Heat treatment process After the step (6) or instead of the step (6), the polyolefin microporous membrane after drying may be heat-treated. The heat treatment stabilizes the crystals and makes the lamellae uniform. As the heat treatment method, a heat setting treatment and / or a heat relaxation treatment can be used. The heat setting treatment is a heat treatment in which the membrane is heated while maintaining its dimensions. The heat relaxation treatment is a heat treatment in which the membrane is thermally shrunk in the MD direction or TD direction during heating. The heat setting treatment is preferably performed by a tenter method or a roll method. For example, an example of a heat relaxation treatment method is the method disclosed in JP-A-2002-256099. The heat treatment temperature is preferably within the range of TCD to the melting point of the polyolefin resin. The melting point can be measured by a differential scanning calorimeter (DSC) based on JIS K7121 (1987).
[0078] (8) Cross-linking and hydrophilic treatment processes Furthermore, the dried polyolefin microporous membrane may be subjected to a crosslinking treatment and a hydrophilization treatment after step (7) or instead of step (7).
[0079] For example, the crosslinking treatment is performed by irradiating the polyolefin microporous membrane with ionizing radiation such as A-rays, B-rays, G-rays, or electron beams. In the case of electron beam irradiation, the electron beam dose is preferably 0.1 to 100 MRAD, and the acceleration voltage is preferably 100 to 300 kV. The crosslinking treatment increases the meltdown temperature of the polyolefin microporous membrane.
[0080] The hydrophilization treatment can be carried out by monomer grafting, surfactant treatment, corona discharge, etc. The monomer grafting is preferably carried out after the crosslinking treatment.
[0081] The polyolefin microporous membrane obtained as described above can be used for various applications such as a filter, a separator for a secondary battery, a separator for a fuel cell, a separator for a capacitor, etc. In particular, when used as a separator for a battery, it has excellent permeability and can provide high safety, and can be more preferably used as a separator for a secondary battery that requires high energy density, high capacity, and high output such as for an electric vehicle. EXAMPLES
[0082] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples. [Measurement method] Thickness The thickness of the polyolefin microporous membrane was measured at any five points within a 50 mm x 50 mm area using a contact thickness gauge, Litematic VL-50 (10.5 mmφ ultrahard spherical probe, measuring load 0.01 N) manufactured by Mitutoyo Corporation, and the average value was recorded as the thickness (μm). [Porosity] A sample of 50 mm × 50 mm square was cut from the polyolefin microporous membrane, and its volume (cm) at room temperature (25°C) was measured. 3 ) and mass (g). These values and the film density (g / cm 3 The porosity of the polyolefin microporous membrane was calculated from the following formula. The membrane density was 0.99 g / cm 3 The calculations were performed assuming a constant value of
[0083] Formula: Porosity (%) = (Volume - Mass / Membrane Density) / Volume x 100 [Puncture strength per 1μm thickness] The puncture strength was measured in accordance with JIS Z 1707 (2019), except that the test speed was 2 mm / sec. Using a force gauge (DS2-20N manufactured by Imada Co., Ltd.), the maximum load (gf) was measured when a polyolefin microporous membrane was punctured in an atmosphere of 25°C with a 1.0 mm diameter needle with a spherical tip (radius of curvature R: 0.5 mm). Using the thickness value measured by the above-mentioned method, the value calculated from the following formula was used as the puncture strength (gf / μm) converted to a thickness of 1 μm.
[0084] Formula: Puncture strength per 1 μm thickness (gf / μm) = Maximum load (gf) / polyolefin microporous membrane thickness (μm) [Air permeability per 1μm thickness] For polyolefin microporous membranes, the air permeability (sec / 100cm) was measured in an atmosphere of 25°C using an Oken air permeability meter (Asahi Seiko Co., Ltd., EGO-1T) in accordance with JIS P-8117:2009. 3 The thickness measured by the above method was used to calculate the air permeability (sec / 100 cm) per 1 μm thickness using the following formula: 3 ) was calculated.
[0085] Formula: Air permeability per 1 μm thickness (sec / 100 cm 3 ) = Air permeability (sec / 100cm 3 ) / polyolefin microporous membrane thickness (μm) [Tensile strength] The tensile strength in the MD direction and the tensile strength in the TD direction were measured using a Shimadzu Corporation universal testing machine AGS-J in accordance with the method of ASTM D882. A rectangular test piece with a width of 10 mm was used as the test piece, and measurements were taken at three arbitrary points on the sample surface in both the MD direction and the TD direction, and the average value was taken as the tensile strength in the relevant direction. [Shutdown temperature] The polyolefin microporous membrane was heated at a heating rate of 5°C / min while measuring the air permeability resistance with an Oken air permeability meter (manufactured by Asahi Seiko Co., Ltd., EGO-1T). The air permeability resistance was measured at the detection limit of 99999 seconds / 100 cm 3 The temperature at which the air reached was taken as the shutdown temperature (°C).
[0086] The measurement cell was composed of an aluminum block and had a thermocouple located directly under the polyolefin microporous membrane. The sample was cut into a 5 cm x 5 cm square and heated while being fixed with an O-ring around the periphery. [Heat shrinkage rate after 8 hours at 105℃] A 5 cm x 5 cm square sample was cut out from the polyolefin microporous membrane so that two sides were parallel to the MD direction. The length of the sample in the MD direction was measured at the center of the sample in the TD direction, and this was defined as the length before MD shrinkage (L 1MD The length of the sample in the TD direction was measured at the center of the MD direction and this was defined as the length before TD shrinkage (L 1TD ) was decided.
[0087] Next, the sample was placed in an oven with the temperature inside the oven set to 105°C and heated, and then removed 8 hours after placement. The MD length was measured at the location where the length before MD shrinkage was measured, and this was defined as the length after MD shrinkage (L 2MD ) was used. In addition, the length in the TD direction was measured at the location where the length before TD shrinkage was measured, and this was used as the length after TD shrinkage (L 2TD Using these values, the thermal shrinkage rate after 8 hours at 105°C was calculated according to the following formula. This measurement was also carried out at three arbitrary points on the sample surface, and the average value was calculated as the thermal shrinkage rate (%) after 8 hours at 105°C.
[0088] Formula: Heat shrinkage rate (%) after 8 hours at 105°C = 100 x (L 1MD -L 2MD +L 1TD -L 2TD ) / (L 1MD +L 1TD ) [Domain diameter in polyolefin microporous membrane] Polyolefin microporous membrane 4The sample was stained with , and a thin section was prepared by microtome method to observe the cross section in the thickness direction-MD direction. The observation was performed using a transmission electron microscope (JEM1400Plus type manufactured by JEOL Ltd.) at an acceleration voltage of 100 kV and a magnification of 50,000. Since the staining conditions were different in the resin A part, the resin B part, and the pore part, an observation image with contrast in light and dark was obtained. In the above observation image, the area of the domain was calculated for the region having a domain-like contrast derived from resin B, and the diameter of the domain was calculated assuming that the cross section of the domain was circular, and the domain diameter was determined. The domain diameter value was measured and calculated as described above for any 10 domains, and the average value was determined as the domain diameter (nm) in the polyolefin microporous membrane. [Thickness reduction rate at 70℃ and pressurized at 2.3MPa, thickness reduction rate / porosity at 70℃ and pressurized at 2.3MPa, and porosity at 70℃ and pressurized at 2.3MPa] A sample was prepared by stacking 100 polyolefin microporous membranes and punching them into a circle with a diameter of 14 mm using a punching machine. Measurements were performed in compression mode using a viscoelasticity measuring device (RSA-G2 manufactured by TA Instruments) with a circular compression jig of φ4 mm. The sample was set on the sample stage, and the inside of the tank was heated to 70°C while the sample was held down with a pressure of 70 KPa using the compression jig. The gap between the measurement jig and the sample stage at the time when the temperature was raised to 70°C was taken as the sample thickness T. 1 After the temperature inside the tank reached 70°C, the compression pressure was changed to 2.3 MPa and held for 1 hour. The value at which the gap between the measurement jig and the sample stage became the narrowest was taken as the sample thickness under pressure T 2 Using the porosity (%) of the polyolefin microporous membrane calculated by the measurement method described above in [Porosity], the membrane thickness reduction rate / porosity when pressurized at 70°C and 2.3 MPa was calculated using the following formula 1, the membrane thickness reduction rate / porosity when pressurized at 70°C and 2.3 MPa was calculated using the following formula 2, and the porosity when pressurized at 70°C and 2.3 MPa was calculated using the following formula 3.
[0089] Formula 1: Film thickness reduction rate (%) at 70°C and 2.3 MPa pressure = 100 × (T 1 -T 2 ) / T 1 Equation 2: Film thickness reduction rate at 70°C and 2.3 MPa pressure / Porosity (-) = 100 × (T 1 -T 2 ) / (T 1 ×porosity) Equation 3: Porosity (%) at 70°C and 2.3 MPa pressure = 100 × {T 1 ×Porosity / 100-(T 1 -T 2 )} / T 2 Example 1 Resin A has a weight average molecular weight (Mw) of 6.0×10 5 60% by mass of high-density polyethylene having a melting point of 136°C, and a weight average molecular weight (Mw) of 2.0 × 10 6 A mixture consisting of 40 mass % of ultra-high molecular weight polyethylene having a melting point of 133° C. was used as resin B. A cyclic olefin copolymer (COC) having a glass transition temperature of 178° C. (COC TOPAS (registered trademark) 6017S-04 manufactured by Polyplastics) was used as resin B.
[0090] A mixture of 17% by mass of resin A, 8% by mass of resin B, 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant, and 74.8% by mass of liquid paraffin was placed in a kneading evaluation test device (Labo Plastomill manufactured by Toyo Seiki Co., Ltd.), and melt-kneaded for 15 minutes at a temperature of 200°C and a cylinder rotation speed of 50 rpm to prepare a polyolefin resin composition. The polyolefin resin composition was sandwiched between Teflon sheets and pressed at 200°C, and then a sample was taken out and sandwiched between metal plates adjusted to 25°C, and cooled to form a gel-like sheet.
[0091] The gel-like sheet obtained was cut into a square of 80 mm square, preheated at 115°C for 300 seconds, and simultaneously biaxially stretched 5 times in the MD direction and 5 times in the TD direction at a stretching temperature of 115°C and a stretching speed of 1000 mm / min (first stretching). The stretched membrane was washed in a washing tank of methylene chloride to remove liquid paraffin, dried in a drying oven adjusted to 20°C, and heat-set (heat treatment) in an electric oven at 120°C for 10 minutes to obtain a polyolefin microporous membrane. Example 2 Resin A has a weight average molecular weight (Mw) of 4.0×10 5 , 60% by mass of branched high-density polyethylene having a melting point of 136°C, and a weight average molecular weight (Mw) of 2.0 × 10 6 A mixture consisting of 40% by mass of ultra-high molecular weight polyethylene having a melting point of 133°C was used. Resin B was not used. A mixture of 25% by mass of Resin A, 0.2% by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane as an antioxidant, and 74.8% by mass of liquid paraffin was charged into a kneading evaluation test device (Labo Plastomill manufactured by Toyo Seiki Co., Ltd.), and melt-kneaded at a temperature of 200°C and a cylinder rotation speed of 50 rpm for 15 minutes to prepare a polyolefin resin composition. The polyolefin resin composition was sandwiched between Teflon sheets and pressed at 200°C, and then a sample was taken out and sandwiched between metal plates adjusted to 25°C, and cooled to form a gel-like sheet.
[0092] The gel-like sheet obtained was cut into a square of 80 mm square, preheated at 115°C for 300 seconds, and sequentially biaxially stretched at a stretching temperature of 115°C and a stretching speed of 1000 mm / min, first 9 times in the MD direction and then 9 times in the TD direction (first stretching). The stretched membrane was washed in a washing tank of methylene chloride to remove liquid paraffin, dried in a drying oven adjusted to 20°C, and heat-set (heat treatment) in an electric oven at 125°C for 10 minutes to obtain a polyolefin microporous membrane. Example 3 A polyolefin microporous membrane was obtained in the same manner as in Example 1, except that a polyolefin resin composition was prepared using a mixture of 20 mass% of Resin A, 5 mass% of Resin B, 0.2 mass% of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)propionate]methane as an antioxidant, and 74.8 mass% of liquid paraffin, and a cyclic olefin copolymer (COC) (COC TOPAS (registered trademark) 6013F-04 manufactured by Polyplastics) having a glass transition temperature of 138°C was used as Resin B. Example 4 A polyolefin microporous membrane was obtained in the same manner as in Example 1, except that a polyolefin resin composition was prepared using a mixture of 20 mass% of Resin A, 5 mass% of Resin B, 0.2 mass% of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)propionate]methane as an antioxidant, and 74.8 mass% of liquid paraffin, using a cyclic olefin polymer (COP) (COP ZEONOR (registered trademark) 1420R manufactured by Zeon Corporation) having a glass transition temperature of 136°C as Resin B. Comparative Example 1 The same procedure as in Example 1 was repeated, except that Resin A was a mixture of high-density polyethylene and ultra-high molecular weight polyethylene in proportions of 80% by mass and 20% by mass, Resin B was not used, and a polyolefin resin composition was prepared using a mixture of 25% by mass of Resin A, 0.2% by mass of the antioxidant tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)propionate]methane, and 74.8% by mass of liquid paraffin, to obtain a polyolefin microporous membrane. Comparative Example 2 Resin A has a weight average molecular weight (Mw) of 6.0×10 5 60% by mass of high-density polyethylene having a melting point of 136°C, and a weight average molecular weight (Mw) of 2.0 × 10 6 The same procedure as in Example 2 was carried out, except that a mixture consisting of 40 mass % of ultra-high molecular weight polyethylene having a melting point of 133° C. was used, to obtain a polyolefin microporous membrane. Comparative Example 3 A polyolefin microporous membrane was obtained in the same manner as in Example 1, except that a polyolefin resin composition was prepared using a mixture of 12 mass% of resin A, 13 mass% of resin B, 0.2 mass% of the antioxidant tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)propionate]methane, and 74.8 mass% of liquid paraffin. Comparative Example 4 The same procedure as in Example 3 was carried out, except that crosslinked acrylic beads (acrylic particles) having an average particle size of 2.2 μm (Art Pearl J-4P, manufactured by Negami Chemical Industrial Co., Ltd.) were used as Resin B, to obtain a polyolefin microporous membrane. (evaluation) The polyolefin resin composition and film-forming conditions used to produce each polyolefin microporous membrane, and the evaluation results of the resulting polyolefin microporous membrane are shown in Table 1. In Table 1, "-" in "Polyolefin resin composition" indicates that the component was not contained. Also, "-" in "Domain diameter in polyolefin microporous membrane" indicates that the presence of a domain could not be confirmed and therefore could not be measured.
[0093] The polyolefin microporous membranes of Examples 1 to 4 all had a value of 0.20 or less, which is expressed as the membrane thickness reduction rate at pressurization at 70°C and 2.3 MPa / porosity, and at the same time, they had good compression resistance and a low shutdown temperature of 140°C or less. Therefore, when used as a separator for a secondary battery, they can provide excellent output characteristics and high safety. On the other hand, the polyolefin microporous membranes of Comparative Examples 1 to 4 had poor compression resistance, high shutdown temperatures, or both, and therefore did not have sufficient output characteristics or battery stability when used as a separator for a secondary battery.
[0094] [Table 1] [Industrial Applicability]
[0095] When the polyolefin microporous membrane of the present invention is used as a separator for a secondary battery, it has excellent charge / discharge characteristics due to its high compression resistance, and can quickly shut down the battery when it abnormally heats up, thereby providing high safety, and therefore can be suitably used as a separator for a secondary battery that is particularly required to have a high capacity.
Claims
1. A polyolefin microporous membrane having a value expressed as a membrane thickness reduction rate / porosity when pressurized at 70°C and 2.3 MPa of 0.20 or less, a shutdown temperature of 140°C or less, and comprising 50 to 99% by mass of a polyethylene-based resin and 1 to 50% by mass of a polymer incompatible with the polyethylene-based resin.
2. The microporous polyolefin membrane according to claim 1 , having a porosity of 35% or more.
3. The microporous polyolefin membrane according to claim 1 or 2, which has a porosity of 30% or more when pressurized at 70°C and 2.3 MPa.
4. A polyolefin microporous membrane described in any one of claims 1 to 3, wherein the polymer that is incompatible with the polyethylene resin is an amorphous polymer.
5. The microporous polyolefin membrane according to any one of claims 1 to 4, wherein the polymer incompatible with the polyethylene resin is a cyclic olefin polymer.
6. The polyolefin microporous membrane according to any one of claims 1 to 5, wherein a first phase made of a polyethylene-based resin has a continuous structure, and a second phase made of a polymer incompatible with the polyethylene-based resin has a discontinuous structure, and the second phase has a domain diameter of 10 to 300 nm.
7. The polyolefin microporous membrane according to any one of claims 1 to 6, which has a heat shrinkage rate of 5% or less after 8 hours at 105°C.
8. Air permeability per 1 μm thickness is 30 seconds / 100 cm 3 The polyolefin microporous membrane according to any one of claims 1 to 7, wherein:
9. The microporous polyolefin membrane according to any one of claims 1 to 8, having a pin puncture strength of 10 gf / μm or more per 1 μm thickness.
10. The microporous polyolefin membrane according to any one of claims 1 to 9, having a thickness of 5 µm or more.
Citation Information
Patent Citations
Film with minute pore and its manufacturing method and use
JP2004161899A
Microporous film made of polyolefin
JP2007262203A
High temperature low heat shrinkable polyolefin monolayer microporous film and method for producing the same
JP2018076475A
Low heat shrinking polyolefin microporous film and its production method
JP2019196470A
Polyolefin microporous membrane, separator for cell, and cell
WO2015194504A1
Cited By
Polyolefin microporous film
JP2022158999A
